The role of a digestive enhancer in improving the growth performance, digestive enzymes activity, and health condition of Nile tilapia (Oreochromis niloticus) reared under suboptimal temperature - Fawzy I. Magouz (2020)
© 2020 Despite the ability of Nile tilapia to resist a wide range of temperatures, the over and suboptimal temperature causes a decline in the growth rates. The use of growth enhancers may lead to an increase in the feeding ability of fish and thus increase the growth and health efficiency under low-temperature conditions. Therefore, Nile tilapia (initial weight, 21 ± 0.01 g) fed four diets supplemented with a digestive enhancer (a mixture of taurine and medium-chain fatty acids) (DME) at 0, 1, 2, and 3 g per kg diet in the present study. The fish were reared under suboptimal temperature (21.3 ± 0.71 °C) for 90 days. Dietary DME significantly increased the growth performance, feed intake, lipase, amylase, and protease activities and lowered the feed conversion ratio in a dose-dependent manner concerning fish fed DME free diet (p < .05). The intestinal morphometry (midgut) displayed increased villus length, width, and the number of goblet cells by DME feeding when compared to the control (p < .05). Besides, fish fed DME displayed normal structure, integrated, and branching villi as well as condensed mucosa and submucosa layers. All the measured haematological and blood biochemical variables showed normal values with insignificant differences among fish fed with or without DME under suboptimal temperature. Interestingly, dietary DME significantly improved the activities of phagocytic and lysozyme in a dose-dependent manner (p = .04 and p = .012). In contrast, the phagocytic index was not affected by the inclusion of DME (p >. 05). Based on the polynomial regression analysis, the inclusion of DME at 1.83 to 2.82 g per kg diet can be used effectively for tilapia reared at suboptimal temperatures to maintain the normal growth rates without a decrease in the physiological and immunological status.